2020
DOI: 10.1002/asia.202000541
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Toolbox to Decode the Microbiota Lexicon

Abstract: The human microbiota deploys a diverse range of molecules and metabolites to engage in chemical communications with the host, mediating fundamental aspects of host health. Studies of the structures and activities of bioactive molecules produced by the microbiota are imperative to address their implications in microbiota associated diseases in human. By drawing experiences from different research fields, chemists and chemical biologists, who are experts in dealing with chemical molecules, are uniquely positione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 104 publications
0
3
0
Order By: Relevance
“…One of the reasons for these low detection rates is the presence of thiols at low concentrations in highly complex human specimens and the limitation of tools to enrich and selectively analyze this compound class with poor ionization properties. 18,19 These unknown thiols can be products of microbial biosynthetic gene clusters (BGCs). 20,21 In a study by Donia et al, more than 3000 BGCs were identified in the microbiomes of healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
“…One of the reasons for these low detection rates is the presence of thiols at low concentrations in highly complex human specimens and the limitation of tools to enrich and selectively analyze this compound class with poor ionization properties. 18,19 These unknown thiols can be products of microbial biosynthetic gene clusters (BGCs). 20,21 In a study by Donia et al, more than 3000 BGCs were identified in the microbiomes of healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
“…These constantly increasing experimental and computational standard libraries contain large sets of metabolite fragmentation pattern and serve as important tools for the characterization of metabolites in any sample type. However, new tools and advanced analyses lead to the identification of yet unidentified and uncharacterized metabolites that are not present in these databases and not directly available for the scientific community [ 13 , 14 ]. The structure of validated metabolites is reported at different levels of confidence and the highest level requires authentic chemical standards [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of these metabolites are still unknown due to the complexity of metabolic processes in this interspecies communication and limited analytical methods. 5,6 The detailed elucidation of the metabolic exchange between the human host and its gut microbiota has a tremendous potential for the discovery of small molecule biomarkers of diseases and bioactive compounds. 7 Amine-containing metabolites have important roles in biological processes and this class of metabolites contains the largest percentage of gut microbiota-derived metabolites.…”
mentioning
confidence: 99%